OPINI AUDIT TAHUN SEBELUMNYA, PERTUMBUHAN PERUSAHAAN DAN PENERIMAAN OPINI AUDIT - Sinaga, Michael Josep; Mila Susanti (Pusat Riset dan Inovasi Nasional, 2023)
The company need an audit opinion to be able to validate the accountability of the company's financial statements to users, so as to be able to produce the right decisions. Therefore, this research aimed to determine the effect of the previous year's audit opinion and the company's growth on the receipt of this year's audit opinion. This research used quantitative data taken from the financial reports of companies listed on the IDX for 2020-2021. It was found that there were 35 companies as a population that entered the trade, service and investment sectors, especially in the tourism, hotel and restaurant sub-sectors. The data collection process founded that there were 27 companies in 2020 that could be processed as samples, while in 2021 there were 29 sample companies. This study used descriptive analysis techniques and correlational inferential statistics. The results of the observations shown that the previous audit opinion had a significant effect on this year's audit opinion. The findings on the company's growth illustrated the absence of a significant influence on the receipt of audit opinions this year. The conclusion that could be drawn from this study was that the auditor in providing an opinion was influenced by the opinion of the previous year, but not influenced by the growth of the company.